Sistem rekabentuk corak dan acuan pinggan - Ng, Chuan Huat (2003)
This research present the design process and integration between Computer Numerical Control (CNC) and Rapid Prototyping (RP) machine to produce a mold for dinnerware and decorative pattern for Malaysia ceramic tableware industry. The research is a collaboration between Kolej Universiti Teknologi Tun Hussein Onn (KUiTTHB) and Oriental Ceramic company Batu Pahat, Johor. To implement the decorative pattern and mould dinnerware, Sistem Rekabentuk Corak dan Acuan Pinggan (SRCAP) was developed. The system was developed using programming language AutoLlSP and a dialog box in AutoCAD software. The parameters involved are the type of dinnerware, material shrinkage, size and shape of decorative pattern. The size of the mold dinnerware were referred to the machine catalogue of the Flatware Making machine available in KUiTTHO. Then the standard size and shape of the dinnerware were referred to the ceramic industrial catalogue. Facilities such as feature library, data entrance, sharing the data in producing the core through the cavity of the mold dinnerware and the decorative pattern arrangement based on the ellipse method was developed in SRCAP. Implementation and analysis tests were conducted to research the design time, user friendly, integrated ability and comment from the user. A mold dinnerware comparison between CNC and RP was also carried out to know the production time and quality of the product. It is found that SRCAP could reduce the design time between 93 to 100 percent. Beside, the quality of the product produced using SRCAP was the same as the manual method. The user friendly in use of the sottware was testified by comments of the users.